2016
DOI: 10.1007/s00404-016-4129-3
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum cathepsin B concentration in pregnant women is associated with preeclampsia

Abstract: The serum levels of cathepsin B levels were increased significantly in preeclamptic women. Correlation with severity of preeclampsia needs further investigation to clarify the role of cathepsin B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Circulating concentrations of cathepsin B and D were determined in a cohort of 72 pregnant women in which 25 were preeclamptic and 47 were normotensive. In accordance with our study, cathepsin B concentrations were found to be significantly increased in preeclamptic women, whereas in contrast to our data, no significant difference was found in cathepsin D concentrations between the preeclamptic and control groups, and no correlation was found between the cathepsin concentrations and the severity of preeclampsia (21) . The differential expression or aberrant release of cathepsin proteases from trophoblasts or other types of cells were suggested to have a key role in the pathophysiology of preeclampsia (21) .…”
Section: Discussionsupporting
confidence: 87%
“…Circulating concentrations of cathepsin B and D were determined in a cohort of 72 pregnant women in which 25 were preeclamptic and 47 were normotensive. In accordance with our study, cathepsin B concentrations were found to be significantly increased in preeclamptic women, whereas in contrast to our data, no significant difference was found in cathepsin D concentrations between the preeclamptic and control groups, and no correlation was found between the cathepsin concentrations and the severity of preeclampsia (21) . The differential expression or aberrant release of cathepsin proteases from trophoblasts or other types of cells were suggested to have a key role in the pathophysiology of preeclampsia (21) .…”
Section: Discussionsupporting
confidence: 87%
“…Another study showed that prolactin fragments with antiangiogenic effects are highly expressed in the placentas of gestational hypertension, whereas the expression of Cat D in the placentas of the gestational hypertension group is significantly decreased [ 33 ]. Kim et al [ 16 , 34 ] found low expression of Cat D in PE serum, and it is believed that insufficient Cat D expression or activity reduces the invasiveness of trophoblast cells. Nakashima et al [ 35 ] also found significantly low expression of Cat D in PE placentas through experiments, and further tests proved that hypoxia can inhibit the expression of Cat D in trophoblast cells.…”
Section: Discussionmentioning
confidence: 99%